2012
DOI: 10.4187/respcare.01428
|View full text |Cite
|
Sign up to set email alerts
|

Exercising Your Patient: Which Test(s) and When?

Abstract: With the introduction of the stair climb test of surgical patients in the 1950s, the role of exercisebased testing as a useful diagnostic tool and an adjunct to conventional cardiopulmonary testing was established. Since then, we have witnessed a rapid development of numerous tests, varying in their protocols and clinical applications. The relatively simple "field tests" (shuttle walks, stair climb, 6-minute walk test) require minimal equipment and technical support, and so are generally available to physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…In these circumstances, some form of exercise evaluation is required. 19 A number of exercise testing protocols have evolved, usually to answer a specific question regarding exercise intolerance. Stair climbing is a simple form of exercise dating back 50 years.…”
Section: Exercise Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In these circumstances, some form of exercise evaluation is required. 19 A number of exercise testing protocols have evolved, usually to answer a specific question regarding exercise intolerance. Stair climbing is a simple form of exercise dating back 50 years.…”
Section: Exercise Testingmentioning
confidence: 99%
“…These include the FOT, 18 enhanced use of transcutaneous P O 2 and P CO 2 sensors (for adults as well as children), uptake of NO to measure D LNO (membrane transfer factor), 44 impedance cardiography to measure cardiac output, 19 and analysis of exhaled NO (F ENO ) to assess airway inflammation. 35 Some technologies are on the horizon that are "brand new" and may have a role in the PFT lab of the future.…”
Section: Pft Lab Of the Futurementioning
confidence: 99%
“…[1][2][3][4][5][6][7] Indeed, peak V O 2 is a robust predictor of outcomes in many cardiopulmonary diseases such as COPD, congestive heart failure, cystic fibrosis, and pulmonary hypertension. [1][2][3]8,9 However, we have observed that there are some patients who achieve higher percent-of-predicted peak work than percent-ofpredicted peak V O 2 , and vice versa. In these cases it is unclear whether to use peak work or peak V O 2 as the parameter by which to judge the patient's exercise capacity.…”
Section: Introductionmentioning
confidence: 70%
“…This is in accordance with the general concept of rating impairment versus disability, 34 wherein the former reflects physiological function, while the latter reflects the ability to perform work in the context of personal and environmental factors: a more global measure. It is important to emphasize, however, that peak V O 2 remains an important measure of cardiovascular conditioning, 35 preoperative risk in lung resection surgery, 36 and a predictor of future cardiopulmonary outcomes, [1][2][3]8,9 and such relationships have not been found for direct measures of work.…”
Section: Discussionmentioning
confidence: 99%
“…However, among patients with COPD, the presence of a low D LCO warrants measurement of exercise O 2 , often in conjunction with a 6-min walk distance test. [23][24][25] Are Measurements of Hyperinflation Helpful?…”
Section: Is D Lco Helpful In Predicting Exercisementioning
confidence: 99%